Identifying the differences of neural correlate on N200 and P300 event related potential (ERP) components from visual stilmuli between extraversion and ambiversion type of personality - Muhammad, Saidah Napisah (2016)
Studies that explore neurophysiological correlates with personality traits have commonly used event-related potential (ERP) during a visual oddball task with results being the main changes in the N200 and P300 components. Besides that, the science of the brain of each personality suggested there are differences in nature and how they react towards stimuli might be differ between personalities. The objectives of this study are to determine the amplitude and latency of P300 ERP component between extravert and ambivert trait of personality from visual stimuli and to determine the amplitude and latency of N200 ERP component between extravert and ambivert trait of personality from visual stimuli using 128-electrode sensor net. Two groups of subjects, one consists of 19 displaying the extraversion trait and the other 20 subjects displaying ambiverts trait. Students with neuropsychological problems and introverts are excluded as a trait controlled. Participants completed a visual oddball task by pushed button’1’ or ‘2’ is see standard (O) or target (X) stimuli respectively. The amplitude and latency of P300 and N200 was observed and determined. The results obtained was analyzed using Mann Whitney test and the Wilcoxon test measured from nine electrode sites. Mann Whitney test revealed that there is no significant difference for amplitude and latency between ambivert and extravert because less electrodes demonstrated the differences between those personalities. However, Wilcoxon Test that used to discriminate the standard and target within personalities has determined that extravert showed more significant differences for amplitude and latency of N200 and P300. However, Chi Square test has proved that there is no association between the significant electrode and the ERP components. The future work may required better explanation of neural processing using different paradigm and methodologies to prove that ambivert has different neural correlate than extravert.